2022
DOI: 10.1108/ijoem-10-2021-1606
|View full text |Cite
|
Sign up to set email alerts
|

Does KAM disclosure make a difference in emerging markets? An investigation into audit fees and report lag

Abstract: PurposeThis study investigates the consequences of the key audit matter (KAM) disclosure requirement by considering two salient audit proxies: audit fees and audit report lag. This investigation is relevant because most auditors worldwide are required to expand their audit report including discussion on key matters faced in the audit engagement. However, the emerging literature on the implications of KAM is inconclusive.Design/methodology/approachUsing a distinctive dataset of 601 year-observations for firms l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 65 publications
(308 reference statements)
0
10
1
Order By: Relevance
“…A previous study by Baatwah et al (2022) found a negative relationship between audit fees and audit report lag. In other words, high audit fees reduce audit report lag.…”
Section: Audit Fees and Audit Report Lagmentioning
confidence: 78%
“…A previous study by Baatwah et al (2022) found a negative relationship between audit fees and audit report lag. In other words, high audit fees reduce audit report lag.…”
Section: Audit Fees and Audit Report Lagmentioning
confidence: 78%
“…Using a UK sample, they report that increasing RMMs in audit reports is associated with a significant increase in audit fees, suggesting that expanded audit report requirements such as KAMs have increased audit effort and audit quality. This finding is asserted by Li et al (2019) and Baatwah et al (2022b), who suggested that audit fees significantly increased following the KAMs disclosure requirement. Using an alternative proxy for audit effort, Baatwah et al (2022b) examined how KAMs disclosure requirements affect the audit report lag for listed firms in the Omani capital market.…”
Section: Prior Research On Key Audit Matters Consequencesmentioning
confidence: 87%
“…This finding is asserted by Li et al (2019) and Baatwah et al (2022b), who suggested that audit fees significantly increased following the KAMs disclosure requirement. Using an alternative proxy for audit effort, Baatwah et al (2022b) examined how KAMs disclosure requirements affect the audit report lag for listed firms in the Omani capital market. They found that KAMs disclosure requirements are associated with a shorter audit report lag while maintaining higher-quality reports, arguing that auditors during KAMs requirements increase their effort by allocating more audit staff and time for audit engagements.…”
Section: Prior Research On Key Audit Matters Consequencesmentioning
confidence: 87%
“…The intention is to focus on issues crucial to stakeholders' understanding of the financial statements and requiring special attention from the auditor. By employing this structured approach, the external auditor aims to enhance the transparency and clarity of the audit report, ensuring that users gain valuable insights into the critical aspects of the audit process and the associated financial reporting risks (Baatwah et al, 2022;Li et al, 2019). Ultimately, the disclosure of KAM contributes to a more informative and meaningful communication between auditors and stakeholders.…”
Section: Identification Of Key Audit Mattermentioning
confidence: 99%